2021
DOI: 10.1186/s12943-021-01398-4
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-modified circIGF2BP3 inhibits CD8+ T-cell responses to facilitate tumor immune evasion by promoting the deubiquitination of PD-L1 in non-small cell lung cancer

Abstract: Background An in-depth understanding of immune evasion mechanisms in tumors is crucial to overcome resistance and enable innovative advances in immunotherapy. Circular RNAs (circRNAs) have been implicated in cancer progression. However, much remains unknown regarding whether circRNAs impact immune escape in non-small-cell lung carcinoma (NSCLC). Methods We performed bioinformatics analysis to profile and identify the circRNAs mediating immune evasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(168 citation statements)
references
References 49 publications
1
145
0
1
Order By: Relevance
“…m6A-modified circIGF2BP3 inhibited the activity of T cells in vitro and restrain antitumor immunity in vivo by upregulating PKP3 to elevate PD-L1 abundance. Furthermore, the inhibition of circIGF2BP3/PKP3 enhanced the effects of anti-PD-1 therapy in a Lewis lung carcinoma mouse model ( 158 ). These works suggested that m6A regulators or m6A-modified non-coding RNA could be a therapeutic target for immunotherapy in combination with PD-L1 inhibitors.…”
Section: Implications For Cancer Drug Therapymentioning
confidence: 99%
“…m6A-modified circIGF2BP3 inhibited the activity of T cells in vitro and restrain antitumor immunity in vivo by upregulating PKP3 to elevate PD-L1 abundance. Furthermore, the inhibition of circIGF2BP3/PKP3 enhanced the effects of anti-PD-1 therapy in a Lewis lung carcinoma mouse model ( 158 ). These works suggested that m6A regulators or m6A-modified non-coding RNA could be a therapeutic target for immunotherapy in combination with PD-L1 inhibitors.…”
Section: Implications For Cancer Drug Therapymentioning
confidence: 99%
“…Nuclear and cytoplasmic extraction reagents (NE-PER, Pierce, IL, USA) were employed to isolate fractional RNA in the cytoplasm and nucleus. Real-time qPCR was performed using SYBR Premix Ex Taq (TaKaRa Bio, Beijing, China) as previously described [ 16 ]. The expression levels of the RNAs of interest were normalized to those of GAPDH, and the primers used in this study are listed in Table S 3 .…”
Section: Methodsmentioning
confidence: 99%
“…CircIGF2BP3 expression is negatively associated with the infiltration of CD8 + T cells, which induces immune escape from CD8 + T cell-mediated killing. Mechanistically, PKP3 upregulated by circIGF2BP3 combines with FXR1 to stabilize OTUB1 mRNA, which increases PD-L1 abundance by promoting its deubiquitination ( 39 ). A study on ovarian cancer has suggested that silencing of circ_C20orf11 suppresses extracellular vesicle (EV)-induced macrophage M2 polarization and enhances sensitivity to CDDP in vivo ( 40 ).…”
Section: Mechanisms Of Drug Resistancementioning
confidence: 99%